Short-term administration of a small thyroxine dose to euthyroid type 2 diabetic patients improves the fasting lipoprotein profile#. (1st January 2017) - Spanoudi, Filio; Vassilatou, Evangeline; Maratou, Eirini; Mitrou, Panagiota; Hatziagelaki, Erifili; Papanas, Nikolaos; Dimitriadis, George; Lambadiari, Vaia
ABSTRACT: Background: Although several studies have assessed the association between thyroid hormones and dyslipidaemia, whether influencing thyroid function improves the lipid profile in euthyroid diabetic patients has not been studied. Methods: Fasting lipids were assessed in 11 euthyroid, treatment naive patients with type 2 diabetes (T2DM) and a micronodular texture of the thyroid gland (age: 43 ± 3.8 years, body mass index (BMI) 27.5 ± 1.4 kg/m 2, triiodothyronine (T3) 119 ± 5.7 ng/dl, thyroxine (T4) 8.13 ± 0.46 μg/dl, thyroid- stimulating hormone (TSH) 1.51 ± 0.14 μIU/ml, free thyroxine (FT4) 1.272 ± 0.047 ng/dl) before and after administration of 50 μg of T4 once daily for 2 months. A placebo was given to 11 age, sex and BMI-matched euthyroid, treatment naive patients with T2DM. Care was taken to avoid even subclinical hyperthyroidism. Results: TSH fell significantly post-treatment (1.51 ± 0.11 vs. 0.79 ± 0.11 μIU/ml, p < 0.0001), but remained within the reference range. Total cholesterol (212 ± 21 vs. 158 ± 10 mg/dl, p = 0.003), low-density lipoprotein cholesterol (146 ± 17 vs. 112 ± 9 mg/dl, p = 0.007), high density lipoprotein cholesterol (51 ± 4 vs. 40 ± 3 mg/dl p = 0.001), triglycerides (93 ± 13 vs. 72 ± 8 mg/dl, p = 0.015), apolipoprotein A1 (167 ± 15 vs. 127 ± 8 mg/dl, p = 0.004), apolipoprotein B (101 ± 13 vs. 72 ± 7 mg/dl, p = 0.009) and lipoprotein (a) (60 ± 15 vs. 41 ± 11 mg/dl p = 0.009) all fell significantly after T4 administration for 2 months. No changes were observed in the placebo group. Conclusions: Small doses of T4 administered to euthyroid patients with T2DM significantly improved lipid levels. This could contribute to a reduced risk of macrovascular complications.